2022
DOI: 10.1007/s00158-022-03393-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of steel–concrete composite bridge based on a transfer function discrete swarm intelligence algorithm

Abstract: Bridge optimization can be complex because of the large number of variables involved in the problem. In this paper, two box-girder steel–concrete composite bridge single objective optimizations have been carried out considering cost and CO$$_{2}$$ 2 emissions as objective functions. Taking CO$$_{2}$$ 2 emissions as an obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The RCPHF design is subject to compliance with the requirements established by the standard regulations [36][37][38]. These, added to a series of technical considerations necessary for the complete verification of the RCPHF, are expressed in general terms through Equation (3). Once the general principles of the considered optimization problem have been detailed, the next step is the complete definition of the problem.…”
Section: Optimization Problem and Computational Model Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RCPHF design is subject to compliance with the requirements established by the standard regulations [36][37][38]. These, added to a series of technical considerations necessary for the complete verification of the RCPHF, are expressed in general terms through Equation (3). Once the general principles of the considered optimization problem have been detailed, the next step is the complete definition of the problem.…”
Section: Optimization Problem and Computational Model Definitionmentioning
confidence: 99%
“…The growth and evolution of societies are directly related to their infrastructure. Thus, the construction, maintenance and demolition of the structures that support a country's economic and social practices are activities intrinsic to its development [3]. The characteristic consumption of large quantities of materials places construction as one of the industries that produce more greenhouse gas emissions, generating around 5% of the total CO 2 emitted yearly [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, metaheuristic methods have emerged as powerful tools in addressing complex problems, particularly those pertaining to the realm of combinatorial challenges. A wide array of applications across various fields, including biology [1,2], logistics [3], civil engineering [4,5], machine learning [6], and many more, serve as compelling evidence of their effectiveness in problem-solving.…”
Section: Introductionmentioning
confidence: 99%
“…Two such algorithms that have been proposed are the Sine Cosine Algorithm (SCA), which uses sine and cosine functions to simulate the movements of individuals, and Cuckoo Search (CS), which models the behavior of natural cuckoo populations. Moreover, recent structural optimization studies have shown that adding a hybridization technique, such as K-means clustering, can improve the behavior of these metaheuristics [310], [311]. The SCA is a swarm intelligence method developed by Mirjalili [233] that employs sine and cosine functions to explore the solution space.…”
Section: Swarm Intelligence: Sca and Csmentioning
confidence: 99%